New species of Hamayulus Fialho, Chamorro-Rengifo & Lopes-Andrade, 2014 (Orthoptera: Tettigoniidae: Listroscelidinae: Hamayulini) from the Northeastern Brazilian Atlantic Rainforest - Mendes, Diego Matheus De Mello; Sobral, Rafael; Neto, Alberto Moreira Da Silva (Zootaxa, 2025)
Hamayulus Fialho, Chamorro-Rengifo & Lopes-Andrade, 2014 (Tettigoniidae: Listroscelidinae: Hamayulini) has, until now, been a monotypic genus and it is the only known genus in Hamayulini. The type-species Hamayulus rufomaculatus Fialho, Chamorro-Rengifo & Lopes-Andrade, 2014 is recorded from the Atlantic Forest biome in Northeast Brazil. In this paper, we describe Hamayulus porangajuba sp. nov., the second species of the genus, from the northeastern Atlantic Forest biome. The new species is described based on an adult male specimen; two female nymphs were also described. A distribution map of the genus is provided as well as comments on the natural history of the new species.